The Influence of Work Behavior, Achievement Motivation, and Work Competence on Employee’s Performance: a Newest Evidence - Athiah Athiah (Institute of Computer Science (IOCS), 2022)
The study is carried out in order to re-confirm the hypothesis validity of the influence of work behaviour, achievement motivation, and working competency onto employees’ work performance, which had been proven formerly by other researchers, among others are Randall S. Schuler (1977), John A. Rubino (1997), J.J. Rodwell et.al. (1998), Musa Djamaludin (2008), Daniel H. Simon et.al. (2009), Amanda Shantz & Gary Latham (2011), Violet T. Ho et.al. (2011), Muhammad Ginanjar (2013), Milah Sopiana (2014), and Rury Riana Rahmah (2014). To do so, the writer of this article underwent a study on seventy respondents working for a vocational high school in Tarumajaya District, Bekasi Regency, West Java Province, Indonesia, called SMKN 1 Tarumajaya. Data collection is done through questionnaire to the target population and at the same time becomes its samples. The study employs quantitative approach, that is, data collected in numerical forms are examined and tested through statistical method of regression analysis. The study finds that an employee’s work behaviour, achievement motivation, and working competency has positive and significant influence onto his work performance. The study also concludes that an employee’s good work behaviour, high achievement motivation, and great working competency will improve and better his work performance.